2017
DOI: 10.1101/217950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospitalized premature infants are colonized by related bacterial strains with distinct proteomic profiles

Abstract: During the first weeks of life, microbial colonization of the gut impacts human immune system maturation and other developmental processes. In premature infants, aberrant colonization has been implicated in the onset of necrotizing enterocolitis (NEC), a lifethreatening intestinal disease. To study variability in the premature infant gut colonization process, genome-resolved metagenomics was conducted on 343 fecal samples collected during the first three months of life from 35 premature infants, 14 of which de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…However, the number of identifications was heavily dependent on the sample type. First, a literature comparison (Supplementary Table S9) confirmed that soil metaproteome studies (Keiblinger et al, 2012; Bagnoud et al, 2016; Bastida et al, 2016; Thorn et al, 2018) identified less proteins and peptides than studies of Hgut (Tanca et al, 2016; Brown et al, 2018; Zhang et al, 2018a; Rechenberger et al, 2019) and BGP (Bize et al, 2015; Hagen et al, 2017; Joyce et al, 2018). Second, it became obvious that sacrificing the fractionation before or after (Hinzke et al, 2019) tryptic digestion resulted in lower number of identifications.…”
Section: Discussionmentioning
confidence: 80%
“…However, the number of identifications was heavily dependent on the sample type. First, a literature comparison (Supplementary Table S9) confirmed that soil metaproteome studies (Keiblinger et al, 2012; Bagnoud et al, 2016; Bastida et al, 2016; Thorn et al, 2018) identified less proteins and peptides than studies of Hgut (Tanca et al, 2016; Brown et al, 2018; Zhang et al, 2018a; Rechenberger et al, 2019) and BGP (Bize et al, 2015; Hagen et al, 2017; Joyce et al, 2018). Second, it became obvious that sacrificing the fractionation before or after (Hinzke et al, 2019) tryptic digestion resulted in lower number of identifications.…”
Section: Discussionmentioning
confidence: 80%
“…However, studies investigating the developing microbiome of preterm infants have revealed conflicting and sometimes counterintuitive results. For the first 3 months of life, Brown et al () examined the gut microbiome of 35 preterm infants and found high variability within infants. In subsequent sampling, some infants had microbial community abundance as unique as those from other infants, and no species were strongly associated with necrotizing enterocolitis (NEC) (Brown et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For the first 3 months of life, Brown et al () examined the gut microbiome of 35 preterm infants and found high variability within infants. In subsequent sampling, some infants had microbial community abundance as unique as those from other infants, and no species were strongly associated with necrotizing enterocolitis (NEC) (Brown et al, ). Dobbler et al () identified low microbial diversity and chaotic succession for infants who developed NEC.…”
Section: Introductionmentioning
confidence: 99%
“…phylogenetic overdispersion). However, overdispersion is far from universal, and multiple studies have shown that extremely close relatives can coexist within the human microbiome [26; 27; 28], and may even be preferentially recruited [29]. Indeed, Darwin's pre-adaptation hypothesis predicts that species with a close relative present in a community will be preferentially recruited, because they are likely to already be adapted to the new environment [23].…”
Section: Introductionmentioning
confidence: 99%